Viva a Cidade : A qualidade do espaço público, à luz da modelagem da informação - Filipe, Sílvia Marina Dias (2019)
Public space is the backbone for urban diversity, as it serves as a stage for public life. Therefore, the quality of public space is a support for citizenship. However, there is a lack of consensus on what a "quality public space" is. Furthermore, a new theoretical and operational perspective has arisen with the modern-day use of Information and Communications Technologies (ICT), which has been changing our behavior and, consequently, the way we use and appropriate the city. How can we, in this way, identify the quality of public spaces for this urban society in constant mutation? This present research arises from the existing restlessness about the role and social responsibility of the professionals that analyze the serious issues that come from the unequal and caustic appropriation of public space. Its aim is to help to think about the influence of information modelling in the processes of public and collective space planning and management, through the development of a methodological process with a computational prototype, which allows the gauging of the quality of a public space, through indicators, parameters and variables listed in the literature. This method is called City Information Modeling (CIM), which associates a Geographic Information System (GIS) with parametrical tools, allowing for the simulation of different scenarios and their respective evaluation. A set of operational parameters and indicators are identified, with the aptitude of being interrelated, correlated and pondered, and capable of dealing, in a coherent way, with the frame of multidisciplinary issues and dynamics which exist in public spaces located by the water (waterfronts). The elected methodology starts from the definition of liveliness, macro-indicator that unfolds in other indicators: density, diversity, connectivity and accessibility. This choice is supported by the concept of "spatial capital", from Lars Marcus (2007), which indicates an urban space value or quality pattern, correlating the measurement of accessibility, density and diversity indicators. This make use spacematrix method developed by Berghauser Pont and Haupt (2009) to analyze density indicator, the theory of space syntax Hillier & Hanson (1984) is used to analyze the accessibility and connectivity indicators, while the diversity indicator, set by the quality of the plinth (the ground floor building façades, the city at eyelevel), is analyzed by land uses. With the computational prototype, it was possible to calculate density indicators (spacematrix), highlighting the open space ratio, and space syntax connectivity indicator, thru a street permeability map. The results indicate that, despite the predominance of multifamily housing, it is a territory endowed with a diversity of economic activities, especially hotels and restaurants. It is also verified that although it is an area very privileged by the abundance of public spaces, it is also guided by the amount of private free spaces, due to the predominance of the typology "closed condominium", that influences the urban network, both in the perception of free space amplitude of, as in the city skyline.